1999
DOI: 10.1046/j.1365-2699.1999.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution of the long‐nosed bat (Leptonycteris curasoae) in North America: does a generalized migration pattern really exist?

Abstract: Summary AimThis paper examines the migration of the tropical nectarivorous bat Leptonycteris curasoae considered as a latitudinal migrant that breeds in south‐west United States and northern Mexico in spring and migrates southward during fall. We tested the hypothesis that the latitudinal migration occurs only locally given by the local availability of bat resources, leading to migratory movements in zones with seasonal scarcity of resources and to resident bat populations where resources are available throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 28 publications
2
84
0
7
Order By: Relevance
“…The two species of Leptonycteris, L. curasoae and L. nivalis, feed primarily on Agave spp. and columnar cacti (37,38). Phyllostomid New World bats are estimated to have evolved Յ15 Mya (39), and bats of the genera Glossophaga and Leptonyceteris diverged from a common ancestor Ϸ2.4 Mya, whereas the two Leptonycteris species diverged Ϸ1.0 Mya (40).…”
Section: Timing Of Speciation In Agave Sensu Lato and Possible Mechanmentioning
confidence: 99%
“…The two species of Leptonycteris, L. curasoae and L. nivalis, feed primarily on Agave spp. and columnar cacti (37,38). Phyllostomid New World bats are estimated to have evolved Յ15 Mya (39), and bats of the genera Glossophaga and Leptonyceteris diverged from a common ancestor Ϸ2.4 Mya, whereas the two Leptonycteris species diverged Ϸ1.0 Mya (40).…”
Section: Timing Of Speciation In Agave Sensu Lato and Possible Mechanmentioning
confidence: 99%
“…During the more than two months of its flowering period, A. horrida produces approximately 3.4 liters of nectar per night per ha, enough to maintain approximately 270 nectarivorous bats (see values of energetic flow proposed by Howell, 1979). Agave species are well known for their capacity to offer enough resources to maintain large POLLINATION BIOLOGY OF AGAVE HORRIDA quantities of pollinators; in central Mexico, their sequential flowering with other chiropterophilous species (agaves and columnar cacti) is likely to be responsible for the presence of resident nectarivorous bats (Rojas-Martínez et al 1999, Morales et al 2007). It has also been suggested that the flowering of nine agave species (including A. horrida) forms a corridor that maintains the migration of Leptonycteris nivalis from central Mexico to the South of the U.S. (Gómez-Ruiz & Lacher 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this area the species is composed of two groups or population with different breeding and behavioral period [1][2]. Populations distribution above parallel 21°N behave as a latitudinal migrant and births occur during the spring [1,3,4], while populations below that parallel are local residents or regional migrant and births occurs at autumn [12,5].…”
Section: Introductionmentioning
confidence: 99%